Biosynthesis of abscisic acid in fungi: identification of a sesquiterpene cyclase as the key enzyme in Botrytis cinerea. (26th July 2018) - Izquierdo‐Bueno, Inmaculada; González‐Rodríguez, Victoria E.; Simon, Adeline; Dalmais, Bérengère; Pradier, Jean‐Marc; Le Pêcheur, Pascal; Mercier, Alex; Walker, Anne‐Sophie; Garrido, Carlos; Collado, Isidro González; Viaud, Muriel
Summary: While abscisic acid (ABA) is known as a hormone produced by plants through the carotenoid pathway, a small number of phytopathogenic fungi are also able to produce this sesquiterpene but they use a distinct pathway that starts with the cyclization of farnesyl diphosphate (FPP) into 2Z, 4E‐α‐ionylideneethane which is then subjected to several oxidation steps. To identify the sesquiterpene cyclase (STC) responsible for the biosynthesis of ABA in fungi, we conducted a genomic approach in Botrytis cinerea . The genome of the ABA‐overproducing strain ATCC58025 was fully sequenced and five STC‐coding genes were identified. Among them, Bcstc5 exhibits an expression profile concomitant with ABA production. Gene inactivation, complementation and chemical analysis demonstrated that BcStc5/BcAba5 is the key enzyme responsible for the key step of ABA biosynthesis in fungi. Unlike what is observed for most of the fungal secondary metabolism genes, the key enzyme‐coding gene Bcstc5/Bcaba5 is not clustered with the other biosynthetic genes, i.e., Bcaba1 to Bcaba4 that are responsible for the oxidative transformation of 2Z, 4E‐α‐ionylideneethane. Finally, our study revealed that the presence of the Bcaba genes among Botrytis species is rare and that the majority of them do not possess the ability to produce ABA.